Evaluation of effectiveness of Ponseti’s method in the clubfoot management under 1-year children: a prospective study - Girotra, Prateek; Kumar, K. Prashanth; Jacob, Rejo Varghese (International Journal of Research in Orthopaedics, 2021)
Background: Congenital talipes equino Varus is common congenital orthopedic foot deformity in children characterized by hindfootequinus, hind foot varus, midfoot cavus, and forefoot adduction deformities. There is a necessity to analyze the number of casts employed in the treatment, compliance of bracing, relapse pattern and percentages of surgical referral under 1 year of age for clear understanding and better practice to achieve successful outcomes. This study aimed to judge the effectiveness of Ponseti in the treatment of clubfoot under 1-year old children. Methods: The patients were selected in the OPD and evaluated for virgin idiopathic clubfoot under 1-year age. Serial casting done weekly by Ponseti method after assessing Pirani and Demeglio score before every cast. Results: In our study all 29 clubfeet that were treated by Ponseti method showed complete correction. Minimum cast being 5 and maximum being 10 casts. Corrected feet were supple, plantigrade and painless of which 1 foot had relapse<3weeks due to ill-fitting shoes. Which was subsequently corrected with repeat tenotomy and cast application. Conclusions: The Ponseti method is a safe, effective, cheap and reproducible method for correction of CTEV which significantly reduces the rate of extensive corrective surgeries for correction of clubfoot under 1-year age. For successful outcome and to prevent relapse, this technique must be applied strictly in accordance to the protocol and parents must be taught the importance of full compliance with bracing. Our series has a short follow up. Longer follow-up is needed for further evaluation of effectiveness of Ponseti method.